Development of Augmented Reality-based Color Learning Application for Pre-school - Mohd So'ad, Siti Nur Amierah; Ismail, Mohd Norasri (Applied Information Technology And Computer Science, 2022)
Learning colors from a young age can help children to differentiate colors and help them express themselves. From a children’s perspective nowadays , physical books are no longer a fun thing. It is because they have been exposed to technology and gadgets. Therefore, the use of augmented reality in learning applications can attract their interest in learning and provide new experiences in using augmented reality. Augmented Reality-based Color Learning Application for Pre-school was developed to help childrens recognize colors. The objective of this project is to design a color learning application for pre-school using augmented reality using marker -based methods. In addition, to develop a mobile -based Color learning using augmented reality for children application.Next, to test the functionality of the application to pre-school.The development model used in this project is the Multimedia Mobile Content Development (MMCD) model which has five phases. In addition, this application is also developed using augmented reality marker (marker-based) to display 3-dimensional objects when the user scan on the color cards. User acceptance testing was implemented by conducting a questionnaire through Google Form to 10 respondents. The results obtained from the test found that 88.25 percent of users evaluated the developed applications as excellent based on the System Usability Scale (SUS) measurement tool Overall, these applications can be classified as applications that successfully achieve the needs of target users.